2019
DOI: 10.3390/molecules24061123
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activities of Quercetin and Its Complexes for Medicinal Application

Abstract: Quercetin is a bioactive compound that is widely used in botanical medicine and traditional Chinese medicine due to its potent antioxidant activity. In recent years, antioxidant activities of quercetin have been studied extensively, including its effects on glutathione (GSH), enzymatic activity, signal transduction pathways, and reactive oxygen species (ROS) caused by environmental and toxicological factors. Chemical studies on quercetin have mainly focused on the antioxidant activity of its metal ion complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
511
0
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 900 publications
(636 citation statements)
references
References 107 publications
12
511
0
17
Order By: Relevance
“…Quercetin has a powerful antioxidant effect and can resist oxidative damage by scavenging ROS. [ 36 ] The intensities of above biomarkers in group DQ2 were decreased or increased than those in group D. These results indicate that quercetin has a protective effect against cadmium‐induced oxidative stress.…”
Section: Discussionmentioning
confidence: 81%
“…Quercetin has a powerful antioxidant effect and can resist oxidative damage by scavenging ROS. [ 36 ] The intensities of above biomarkers in group DQ2 were decreased or increased than those in group D. These results indicate that quercetin has a protective effect against cadmium‐induced oxidative stress.…”
Section: Discussionmentioning
confidence: 81%
“…The nanotechnology based strategies are believed to improve the solubility and bioactivity of nutraceuticals. Furthermore, there are few reports available on antioxidant activity of curcumin and quercetin . To the best of our knowledge, antioxidant activity for other nutraceuticals studied in the present investigation has not been yet reported.…”
Section: Resultsmentioning
confidence: 82%
“…Furthermore, there are few reports available on antiox-idant activity of curcumin and quercetin. [24][25] To the best of our knowledge, antioxidant activity for other nutraceuticals studied in the present investigation has not been yet reported. This prompted us to investigate antioxidant activity of 1-6 NPs and corresponding bulk compounds using in vitro 2,2-diphenyl-1picrylhydrazyl (DPPH) and nitric oxide (NO) radical scavenging assays.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that phenolic hydroxyl groups contribute to the free radical scavenging activity of the molecules (Bors et al, 1990). The health benefits of quercetin are generally attributable to its antioxidant action positively impacting on glutathione and reactive oxygen species (ROS) (Xu et al, 2019). The anti-oxidant action is in part mediated by the modulation of enzymes associated with oxidative stress like acetylcholinesterase and butyrylcholinesterase (Xu et al, 2019).…”
Section: Glycosylated Flavonoidsmentioning
confidence: 99%